Use of Full Diallel Cross to Estimate Crossbreeding Effects in Laying Chickens - Razuki, Waleed M.; AL-Shaheen, Sajida A. (International Journal of Poultry Science, 2011)
Three genotype of chickens (one Iraqi local named Brown line, BR and two adapted exotic breeds named White Leghorn, WL and New Hampshire, NH) were crossed in a 3 x 3 diallel mating (nine combinations) to estimate their crossbreeding effect for Body Weight (BW), age at Sexual Maturity (ASM), egg production and egg weight. All chicks tested in this experiment originated from parents divided into 3 groups. Each group included 864 hens from three genotypes (288 hens for each genotype) and 108 cocks from the genotype used in sire position (1 male: 8 females). Approximately 3600 unsexed day old chicks (400 chicks per combination) were used. At 28 days of age, chicks were sexed and result about 180 females per combination. Females (45 per pen) were weighed and assigned to their cross in 36 pens (4 pens per combination). At 126 days of age, 25 pullets per pen were housed until the end of experiment. The NH purebred had higher BW compared with WL or BR at all ages. BR x NH cross had heaviest BW at ages 28, 56, 84 and 112 days but not at sexual maturity which exhibited reduction in BW. The ASM in BR purebred was earlier (141.25 days) than WL (153.25 days) and NH (154 days) purebreds. The WL x NH cross and NH x WL reciprocal cross exhibited higher egg number than purebred or other crosses. The WL purebred achieved the highest Egg Weight (EW) than other purebred. The line heterosis is significant only at day old BW in WL breed (positive) and BR line (negative), whereas, the others ages was not showed any line heterosis. Average heterosis of BW was positive at all ages, except at day old which was negative and ranged from -2.03 at day old to 39.58 at sexual maturity. The line heterosis of age at sexual maturity and egg weight was non significant, while, the line heterosis of egg production was significantly positive in NH line and was negative in BR line. All combinations (crosses or reciprocal) showed a positive heterosis in egg production ranged from 2.77 to 8.75% with average heterosis is significant (3.20). All combinations (crosses or reciprocal) showed a negative heterosis in egg weight from -0.15 to -3.66 with significant average heterosis (-1.21). Reciprocal effects were significant for BW and ASM and not in egg production or in egg weight. The GCA of BW was significantly greater and positive for NH breeds at all ages than WL and BR lines were exhibited significantly negative GCA. GCA for ASM, egg production and egg weight of WL breeds gave the highest (positive) significant values compared with the BR line which was exhibited lowest (negative) values of these traits. Maternal effects of BW and ASM were significant for WL and BR dams. There were non significant in egg production and egg weight due to maternal effect. The direct genetic effect on BW were negatively significant for WL and BR and positively significant for NH. Direct genetic effects on ASM and egg production were non significant and significant on egg weight. Estimations of SCA of BW, ASM, egg production and egg weight varied from positive to negative depended on cross type. This study suggested that use the crossbreeding tools to develop new synthetic strains suitable to Iraqi harsh conditions with acceptance performance.